Physical activity and tobacco smoking in the German adult population - Daniel Kotz; Sarah Jackson; Stephanie Klosterhalfen; Zeynep Acar (BMJ Open Sport & Exercise Medicine, 2024)
Background Physical inactivity and tobacco smoking remain the leading causes of morbidity and mortality worldwide. In Germany, smoking prevalence is high at around 30%, and only 45% achieve the WHO recommendation for physical activity (PA). Understanding how smoking and physical inactivity co-occur can inform interventions targeting these behaviours.Methods We analysed data from 4073 adults (≥18 years) participating in a national household survey between April and July 2022. We tested the association between PA level (not=reference/low/medium/very active) and smoking status (never=reference/ex/current smoker). Among current smokers, we tested associations between PA level and cigarettes smoked per day, time spent with and strength of urges to smoke and motivation to stop smoking.Results Overall, 29.9% (95% CI=28.5; 31.4) reported no leisure-time PA; among current smokers, it was 39.8% (95% CI=37.3; 42.4). Higher PA levels were associated with lower odds of being a current versus never smoker (OR=0.74, 95% CI=0.69; 0.79). Among current smokers, higher PA levels were associated with smoking fewer cigarettes per day (β=−0.98, 95% CI=−1.39; −0.56), weaker urges to smoke (OR=0.81, 95% CI=0.74; 0.89) and higher motivation to stop smoking (OR=1.13, 95% CI=1.02; 1.24). The association between PA and time spent with urges to smoke was not statistically significant (OR=0.93, 95% CI=0.85; 1.02).Conclusion People who are more physically active are less likely to smoke. Current smokers with higher PA levels smoke less, are less dependent and are more motivated to quit. Further research is required to determine whether these associations are causal and, if so, whether interventions to increase PA could help people to quit smoking.